Safety of cold polypectomy for < 10 mm polyps at colonoscopy: a prospective multicenter study - Repici, A.; Hassan, C.; Vitetta, E.; Ferrara, E.; Manes, G.; Gullotti, G.; Princiotta, A.; Dulbecco, P.; Gaffuri, N.; Bettoni, E.; Pagano, N.; Rando, G.; Strangio, G.; Carlino, A.; Romeo, F.; de Paula Pessoa Ferreira, D.; Zullo, A.; Ridola, L.; Malesci, A. (Endoscopy, 2012)
Background: Cold polypectomy techniques (without electrocautery) by means of biopsy forceps or snare are widely adopted for the removal of subcentimetric polyps. However, few data are available on the safety of this approach. The aim of this study was to assess the safety of cold polypectomy for subcentimetric polyps, as well as the rate of advanced neoplasia in these lesions.Patients and methods: In a prospective multicenter trial, consecutive patients with at least one < 10-mm polyp at colonoscopy were prospectively included. All of the < 10-mm polyps detected within the study period were removed by cold polypectomy. The rates of immediate or delayed bleeding and other complications were assessed at 7 and 30 days after cold polypectomy by telephone calls. The rate of advanced histology was also assessed. Predictive variables of postpolypectomy bleeding or advanced neoplasia were identified by multivariate analysis.Results: A total of 1015 < 10-mm polyps in 823 patients (15.5 % on antiplatelet agents) were removed. Of these, 822 (81 %) were ≤ 5 mm and 193 (19 %) were 6 – 9 mm. Immediate postpolypectomy bleeding occurred in 18 patients, corresponding to a per-patient and per-polyp bleeding rate of 2.2 % (95 % confidence interval [CI] 1.2 % – 3.2 %) and 1.8 % (95 %CI 1 % – 2.6 %), respectively. Therapy with antiplatelet agents (odds ratio [OR] 4; 95 %CI 1.5 – 10.6) and larger polyp size (OR 2; 95 %CI 1.1 – 6.9) were independent predictors of bleeding. Bleeding was successfully treated by endoscopic hemostasis in all cases and required no further medical intervention. Advanced neoplasia prevalence in polyps ≤ 5 mm was as high as 8.7 %.Conclusions: The results from this study showed the high safety of a cold polypectomy approach for subcentimetric polyps. This was due to the low rate of postpolypectomy bleeding and to the high efficacy of endoscopic hemostasis in its treatment. The high rate of advanced neoplasia in polyps ≤ 5 mm should prompt some caution on the management of these lesions following detection at computed tomography colonography or colon capsule endoscopy.